A new genus and species of Ingolfiellidae (Crustacea, Ingolfiellida) from the hyporheic zone in the Sierra de la Ventana, and its biogeographic relevance - Rodriguez, Marianela; Armendáriz, Laura C.; Capítulo, Alberto Rodrígues (Zootaxa, 2017)
With the purpose of collecting macroinvertebrates for benthic studies of hill streams of the Argentinean Pampean ecoregion, a sampling program was performed in different seasons during 2015. The ingolfiellid crustaceans described in this paper were found only in May 2015 in a sector of the rithron of the Ventana Stream located below the point of the upwelling of hyporheic water, 50 m upstream where the stream is covered by larger conglomerates. The specimens (5 females and 4 males) were measured and photographed, and some were dissected and mounted in Euparal. Appendages of head, pereion and pleon were illustrated. The analysis of the examined material allowed us to conclude that it constitutes a new taxon, Yacana ventania n. gen. n. sp., enlarging the distribution of the family Ingolfiellidae in South America. Characteristics: body long and thin; without eyes; short antennae; inner seta of the outer lobe of maxilla1 is bi-dentate, vestigial molar process and serrations on one side, three spine row elements decreasing in size and the last one toothed; labium present; gnathopod 1 and 2 with a notch on the inner side of the carpus, the carpus of gnathopod 1 has three spines, the proximal one is on the top of a finger-shaped process, while the carpus of gnathopod 2 presents just two spines, propodus in both gnathopods with finger-shaped process at its distal end, a tiny spine and a seta; pereiopods dissimilar, with seta and terminal claw; pereiopod 7 differs from the others in size, number and arrangement of its setae. Uropod 2 longer than uropod 1, uropod 3 small and uniramous; sexual dimorphism clearly present in pleopods and uropod 2 because the females present more rows of setae than males, and probably in the setation of pereiopod 7. Sizes of specimens varied between 3–8.8 mm. The cladistic analysis (TNT) demonstrates that Yacana ventania n. gen. n. sp. is closely related to South African genera because of the vestigial mandibular palp, also the new taxon here described shared the sexual dimorphism with Stygobarnardia and Trogloleleupia, its discovery gaining relevance on biogeographical aspects and providing new evidence to the theory of continental drift. Type specimens are deposited in the Carcinology Collection of the División Zoología Invertebrados, Museo de La Plata, Argentina.